Event-Related Desynchronization During Mirror Visual Feedback: A Comparison of Older Adults and People After Stroke - Fong, Kenneth N. K.; Ting, K. H.; Zhang, Jack J. Q.; Yau, Christina S. F.; Li, Leonard S. W. (Frontiers in Human Neuroscience, 2021)
The event-related desynchronization (ERD), as a proxy for mirror neurons activity, has been used as a neurophysiological marker for motor execution after mirror visual feedback (MVF). Using EEG, this study investigated the ERD upon the immediate effects of a single session MVF in unimanual arm movements compared with the ERD effects occurring without a mirror, in two groups: stroke patients with left hemiplegia and their healthy counterparts. During EEG recordings, each group performed one session of mirror therapy training in three task conditions: with a mirror, with no mirror, and with a covered mirror. An asymmetry index was calculated from the subtraction of the event-related spectrum perturbations between the C3 and C4 electrodes located over the sensorimotor cortices contralateral and ipsilateral to the moved arm. Results of the effect of task versus group in contralateral and ipsilateral motor areas showed that there was a significant effect of task condition at the contralateral motor area in the high beta band (17-35 Hz) at C3. The high beta ERD showed that the suppression was greater over the contralateral hemisphere than it was over the ipsilateral hemisphere in both study groups. The magnitude of low beta (12-16 Hz) ERD in patients with stroke was more suppressed in contralesional C3 under the no-mirror compared to that of the covered-mirror and similarly more suppressed in ipsilesional C4 ERD under the no-mirror compared to that of the mirror condition. The correlation analysis revealed that the magnitude of ERSP power correlated significantly with arm severity in the low and high beta bands in patients with stroke, and a higher asymmetry index in the low beta band were associated with higher arm functioning under the no-mirror condition. There was a shift in sensorimotor ERD towards the contralateral hemisphere as induced by MVF accompanying unimannual movement in both stroke patients and healthy controls. The use of ERD in the low beta band as neurophysiological marker to indicate the relationships between the amount of MVF-induced ERD attenuation and motor severity, and outcome indicator for improving stroke patients’ neuroplasticity in clinical trials using MVF are warranted to be explored in future.